The Relationship between Ustadz Supervision and Student Discipline in Pondok Tahfizh Darul Qur'an Surau Polak Botuang Nagari Pangian Lintau Buo District Tanah Datar District - Veronika, Nadya; Jamaris, Jamaris (Universitas Negeri Padang, 2023)
This research was motivated by the low discipline of the students at the Tahfizh Darul Qur'an Islamic Boarding School, Surau Polak Botuang Nagari Pangian, Lintau Buo District, Tanah Datar Regency. This is presumably due to the low level of supervision of students of Ustadz. Aims to find out of Ustadz supervision, students discipline and the relationship between the two variables. This type of research is quantitative research with a correlational approach. The population of the study were all students who were active at Pondok Tahfizh, totaling 96 students. The research sample was taken based on cluster sampling with total 76 samples. The data collection technique is questionnaire. The data analysis technique in this study uses the percentage and product moment formulas. The results showed that (1) supervision of Ustadz was still low, (2) discipline of students was still low, and (3) there is a significant relationship between supervision by Ustadz and discipline of students. Based on this research, it hoped that (1) It is suggested to the managing institution of Pondok Tahfizh Darul Qur'an Surau Polak Botuang to strengthen supervision and monitor the implementation of regulations so that they are appropriate and on target. (2) It is recommended that ustadz be more disciplined in enforcing regulations, increasing learning and supervising congregational prayers for students so that the vision and mission of Tahfizh Darul Qur'an Islamic boarding school Surau Polak Botuang is realized. (3) It is recommended that students be more disciplined in complying with the regulations that have been made by the ustadz, so that students get used to these habits from an early age so they are able to apply them both at Pondok Tahfizh Darul Qur'an or at home.Keywords: Supervision Ustadz, Student Discipline